LANGUAGE, MEMORY, AND HISTORICAL RECONSTRUCTION IN MAARTEN HIDSKES' DI BELANDA TAK SEORANG MEMPERCAYAI SAYA - Widodo, Jordy Satria; Rahayu, Eka Murti (Journal Albion : Journal of English Literature, Language, and Culture, 2024)
This research examines the interconnectedness of language, memory, and literature through Maarten Hidskes' book Di Belanda Tak Seorang Mempercayai Saya: Korban Metode Westerling di Sulawesi Selatan 1946-1947. The study investigates how Hidskes reconstructs his father’s involvement in the 1946 South Sulawesi violence, focusing on the role of language in shaping memory and historical narrative. By analyzing the author’s use of limited personal memories, interviews, letters, and archival documents, this work explores how fragmented historical accounts are pieced together through linguistic resources. The research applies theories from memory studies, particularly the dynamic interplay between memory and language (Echterhoff, 2008) and the concept of "Verbal Overshadowing" (Schooler et al., 1997), to understand how language affects memory retrieval and narrative construction. The study also contextualizes Hidskes' approach within the broader literary tradition of memory studies, comparing his narrative techniques with other works that address the relationship between language, memory, and history. This research sheds light on how language not only represents but also constructs memory, especially in post-conflict societies where historical narratives are often fragmented and contested.